Identification and Functional Analysis of G Protein-Coupled Receptors in 20-Hydroxyecdysone Signaling From the Helicoverpa armigera Genome - Li, Yan-Li; Li, Yan-Xue; Wang, Xiao-Pei; Kang, Xin-Le; Guo, Ke-Qin; Dong, Du-Juan; Wang, Jin-Xing; Zhao, Xiao-Fan (Frontiers in Cell and Developmental Biology, 2021)
G protein-coupled receptors (GPCRs) are the largest family of membrane receptors in animals and humans, which transmit various signals from the extracellular environment into cells. Studies have reported that several GPCRs transmit the same signal; however, the mechanism is unclear. In the present study, we identified all 122 classical GPCRs from the genome of Helicoverpa armigera, a lepidopteran pest species. Twenty-four GPCRs were identified as upregulated at the metamorphic stage by comparing the transcriptomes of the midgut at the metamorphic and feeding stages. Nine of them were confirmed to be upregulated at the metamorphic stage. RNA interference in larvae revealed the prolactin-releasing peptide receptor (PRRPR), smoothened (SMO), adipokinetic hormone receptor (AKHR), and 5-hydroxytryptamine receptor (HTR) are involved in steroid hormone 20-hydroxyecdysone (20E)-promoted pupation. Frizzled 7 (FZD7) is involved in growth, while tachykinin-like peptides receptor 86C (TKR86C) had no effect on growth and pupation. Via these GPCRs, 20E regulated the expression of different genes, including Pten (encoding phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase), FoxO (encoding forkhead box O), BrZ7 (encoding broad isoform Z7), Kr-h1 (encoding Krüppel homolog 1), Wnt (encoding Wingless/Integrated) and cMyc, with hormone receptor 3 (HHR3) as their common regulating target. PRRPR was identified as a new 20E receptor using a binding assay. These data suggested that 20E, via different GPCRs, regulates different gene expression to integrate growth and development.